Pan-serotype Reduction in Progression of Streptococcus pneumoniae to Otitis Media After Rollout of Pneumococcal Conjugate Vaccines. (29th July 2017) - Lewnard, Joseph A; Givon-Lavi, Noga; Weinberger, Daniel M; Lipsitch, Marc; Dagan, Ron
Abstract : Pneumococcal progression from carriage to otitis media declined following rollout of PCV7/13 in Israel. Vaccine-targeted and non-vaccine serotypes showed lower progression rates. Early-life otitis media episodes, historically often caused by PCV7/13-targeted serotypes, may exacerbate children's future susceptibility to otitis media. Abstract: Background: Reductions in otitis media (OM) burden following rollout of pneumococcal conjugate vaccines (PCVs) have exceeded predictions of vaccine impact. In settings with active surveillance, reductions in OM caused by vaccine-targeted pneumococcal serotypes have co-occurred with reductions in OM caused by other pathogens carried in the upper-respiratory tract of children. To understand these changes, we investigated the progression of vaccine-targeted and non-vaccine pneumococcal serotypes from carriage to OM before and after vaccine rollout. Methods: Nasopharyngeal carriage prevalence of pneumococcus was monitored in prospective studies of Bedouin and Jewish children <3 years old in southern Israel between 2004 and 2016. Incidence of OM necessitating middle-ear fluid culture (predominantly complex OM including recurrent, spontaneously-draining, non-responsive, and chronic cases) was monitored via prospective, population-based active surveillance. We estimated rates of pneumococcal serotype-specific progression from carriage to disease before and after rollout of PCV7/13, measured as OM incidence per carrier. We pooled serotype-specific estimates using Bayesian random-effects models. Results: On average, rates of progression declined 92% (95% credible interval: 79–97%) and 80% (46–93%) for PCV7/13 serotypes among Bedouin and Jewish children <12 months old, respectively, and 32% (–58–71%) and 61% (–5–86%) among children aged 12-35m. For non-vaccine serotypes, rates of progression among Bedouin and Jewish children aged <12m declined 74% (55–85%) and 43% (4–68%), respectively. Conclusions: Vaccine-targeted and non-vaccine pneumococcal serotypes showed lower rates of progression to complex OM after rollout of PCV7/13. Early-life OM episodes historically associated with vaccine-serotype pneumococci may impact the susceptibility of children to OM progression.